The effect of carbohydrate ingestion following eccentric resistance exercise on AKT/mTOR and ERK pathways: A randomized, double-blinded, crossover study - Figueiredo, V. C.; Farnfield, M. M.; Ross, M. L. R.; Gran, P.; Halson, S. L.; Peake, J. M.; Cameron-Smith, D.; Markworth, J. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Purpose: To determine the acute effects of carbohydrate (CHO) ingestion following a bout of maximal eccentric resistance exercise on key anabolic kinases of mammalian target of rapamycin and extracellular signal-regulated kinase (ERK) pathways. The authors` hypothesis was that the activation of anabolic signaling pathways known to be upregulated by resistance exercise would be further stimulated by the physiological hyperinsulinemia resulting from CHO supplementation. Methods: Ten resistance-trained men were randomized in a crossover, double-blind, placebo (PLA)-controlled manner to ingest either a noncaloric PLA or 3 g/kg of CHO beverage throughout recovery from resistance exercise. Muscle biopsies were collected at rest, immediately after a single bout of intense lower body resistance exercise, and after 3 hr of recovery. Results: CHO ingestion elevated plasma glucose and insulin concentrations throughout recovery compared with PLA ingestion. The ERK pathway (phosphorylation of ERK1/2 [Thr202/Tyr204], RSK [Ser380], and p70S6K [Thr421/Ser424]) was markedly activated immediately after resistance exercise, without any effect of CHO supplementation. The phosphorylation state of AKT (Thr308) was unchanged postexercise in the PLA trial and increased at 3 hr of recovery above resting with ingestion of CHO compared with PLA. Despite stimulating-marked phosphorylation of AKT, CHO ingestion did not enhance resistance exercise-induced phosphorylation of p70S6K (Thr389) and rpS6 (Ser235/236 and Ser240/244). Conclusion: CHO supplementation after resistance exercise and hyperinsulinemia does not influence the ERK pathway nor the mTORC1 target p70S6K and its downstream proteins, despite the increased AKT phosphorylation.